Evaluation of Chlorogenic Acid Supplementation in Koi (Cyprinus carpio) Diet: Growth Performance, Body Color, Antioxidant Activity, Serum Biochemical Parameters, and Immune Response. (12th May 2022) - Xu, Guanling; Xing, Wei; Yu, Huanhuan; Jiang, Na; Ma, Zhihong; Luo, Lin; Li, Tieliang
Abstract : A ten-week feeding trial was performed to evaluate the effects of chlorogenic acid (CGA) on the growth, body color, antioxidant activity, serum biochemical parameters, and immune response of koi. Five diets were formulated to contain 0 (control), 200 (CGA-2), 400 (CGA-4), 600 (CGA-6), and 800 (CGA-8) mg/kg CGA for the rearing of experimental fish. By means of an analysis by polynomial orthogonal contrasts, it was determined that dietary supplementation with CGA had no significant effects on the growth performance of koi (P > 0.05 ), while body color indices (redness, yellowness, and lightness) showed a linear order polynomial (P < 0.05 ). A quadratic response was found for the relationship between total carotenoid in scale of koi and dietary CGA levels, with an optimum level of 381.84 mg/kg. Dietary CGA levels and lysozyme activity showed a cubic relationship polynomial model, with an optimum level of 383.89-975.73 mg/kg. TGF- β expression in the head-kidney of koi was obviously improved by 600 mg/kg CGA diet (P < 0.05 ). And in regards to effect in serum, SOD and CAT activities was best explicated by a linear order polynomial, while the quadratic and cubic relationship polynomial models represented the GSH and GSH-Px activities, which the optimal supplementation level of CGA was estimated at 550.78 and 231.74-782.66 mg/kg, respectively. The relationship between ALT activity and CGA supplementation was best explicated by quadratic relationship polynomial, with an optimum level of 522.78 mg/kg. Based on the model observed, 522.78-600 mg/kg CGA was the recommended supplementation in diet that improved the body color, antioxidant activity, biochemical parameters, and immune response of koi.